2017
DOI: 10.1016/j.jid.2016.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CD109 in the Epidermis Differentially Regulates ALK1 Versus ALK5 Signaling and Modulates Extracellular Matrix Synthesis in the Skin

Abstract: Transforming growth factor-β (TGF-β) is a multifunctional growth factor involved in many physiological processes including wound healing and inflammation. Excessive TGF-β signaling in the skin has been implicated in fibrotic skin disorders such as keloids and scleroderma. We previously identified CD109 as a TGF-β co-receptor and inhibitor of TGF-β signaling and have shown that transgenic mice overexpressing CD109 in the epidermis display decreased scarring. In certain cell types, in addition to the canonical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
21
0
1
Order By: Relevance
“… 44 47 CD109 is a membrane protein, approximately 180 kDa, which binds to TGF-β and represses TGF-β signaling in human keratinocytes. 48 51 Because curcumin and proteins such as CD109, NGF, and BDNF are unstable in biological environments, 52 , 53 it is advantageous to incorporate them into nanocarriers to protect them from hydrolytic and enzymatic cleavage to reach the site of injury.…”
Section: Introductionmentioning
confidence: 99%
“… 44 47 CD109 is a membrane protein, approximately 180 kDa, which binds to TGF-β and represses TGF-β signaling in human keratinocytes. 48 51 Because curcumin and proteins such as CD109, NGF, and BDNF are unstable in biological environments, 52 , 53 it is advantageous to incorporate them into nanocarriers to protect them from hydrolytic and enzymatic cleavage to reach the site of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Vorstenbosch et al . reported that CD109, a glycosylphosphatidylinositol (GPI)-anchored protein, directly interacts with ALK5 and ALK1 and inhibits Smad2/3 activation while enhancing Smad1/5 activation in keratinocytes 41 . On the other hand, it was reported that reduced levels of expression of Bmal1, an essential clock transcription activator, increased TGF-β–mediated phosphorylation levels of Smad1/5/8 but decreased phosphorylation levels of Smad2/3 in primary human articular chondrocytes and C3H10T1/2 cells 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested that K14‐CD109 transgenic mice were resistant to bleomycin‐induced skin fibrosis and showed reduced dermal thickness and decreased fibrotic response in wounds as compared with WT mice. Interestingly, these results were accompanied by increases in STAT3 signaling in CD109‐deficient mice and decreases in TGF‐β signaling in K14‐CD109 transgenic mice …”
Section: Cd109 Is a Membrane Protein Expressed In Malignant Tumorsmentioning
confidence: 99%
“…CD109 is a multifunctional coreceptor that promotes tumor initiation, progression, and metastasis Although CD109 function has been extensively studied, its detailed biological role remains unclear. The primary function of CD109 reportedly involves downregulating transforming growth factor (TGF)-β signaling through its binding to TGF-β receptor I [activin receptor-like kinase (ALK)5], 53 TGF-β, 54 ALK1, 55 and 78-kDa glucose-regulated protein (GRP78) 56 in vitro. Both GPI-anchored CD109 and soluble CD109 bind to TGF-β receptors and attenuate TGF-β-induced SMAD2/3 phosphorylation (Fig.…”
Section: Cd109 Is Secreted In Its Truncated Form or As A Component Ofmentioning
confidence: 99%
See 1 more Smart Citation